Pengaruh Citra Merek, Kepuasan Konsumen dan Promosi Digital Terhadap Loyalitas Pelanggan Sepatu Merek Adidas: Studi pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Wijaya Kusuma Surabaya - Dewantoro Harsono; Husni Indrawati Wijaya Putri (Masyarakat Ekonomi Syariah Bogor, 2026)
Business competition in shoe products has experienced very rapid development in the current era, many shoe brand products have emerged and competed in the market. Adidas brand shoes are one of the many brands used by consumers as one of their favorite shoe prima dona. The purpose of this study is to determine the effect of brand image, consumer satisfaction, and digital promotion on customer loyalty of Adidas brand shoes (a study on students of the Faculty of Economics and Business, Wijaya Kusuma University, Surabaya). The approach used is quantitative which focuses on testing the relationship between variables. The population of this study was aimed at all students of the Faculty of Economics and Business, Wijaya Kusuma University, Surabaya, with a total of 424 students. The sample used was Purposive Sampling with the criteria of customers who own or use Adidas brand shoes, customers aged 20-25 years and active students of the Faculty of Economics and Business at Wijaya Kusuma University, Surabaya. 100 respondents were samples processed by distributing online questionnaires via Google Form as data collectors. The data were processed using IBM Statistic SPSS version 23. The data analysis technique used was multiple linear regression analysis. The results of the t-test hypothesis testing indicate that the first hypothesis, brand image, has no significant effect on customer loyalty for Adidas shoes and is unacceptable. The second hypothesis, consumer satisfaction, has a significant effect on customer loyalty for Adidas shoes and is acceptable. The third hypothesis, digital promotion, has a significant effect on customer loyalty for Adidas shoes and is acceptable.